1989
DOI: 10.1080/07328308908047997
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies on Sialoglycoconjugates. 3: Synthesis of 5-Acetamido-3,5-Dideoxy-l-Arabino-2-Heptulosonic Acid Derivatives and Analogs

Abstract: 5-Acetamido-3,5-dideoxy-~-arabino-2-heptulosonic acid derivativesand analogs (shorter carbon-chain analogs of N-acetylneuraminic acid) were synthesized. Periodate oxidation followed by sodium borohydride reduction and 2-acetylation of methyl [2-(trimethylsilyl)ethyl 5-acetamido-3,5-dideoxy-g~ycero-a-~-galacto-2-nonulopyranosid)onate (3) , prepared by condensat ion of the 2-$-chloro derivative of pentaacetylneuraminic acid methyl ester (1) with trimethylsilylethanol and subsequent 2-deacetylation, gave methyl (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…4c,16 Diol 14 was prepared as follows (Scheme 2). The starting a-benzyl sialoside 8 was synthesized from chloride 2 and benzyl alcohol according to the described procedure 17 followed by de-O-acetylation. Treatment of 8 with 2,2-dimethoxypropane and CSA in acetone afforded 8,9-isopropylidene derivative 9 which was selectively benzoylated at O-4 with benzoyl chloride to give monobenzoate 10.…”
Section: Figurementioning
confidence: 99%
“…4c,16 Diol 14 was prepared as follows (Scheme 2). The starting a-benzyl sialoside 8 was synthesized from chloride 2 and benzyl alcohol according to the described procedure 17 followed by de-O-acetylation. Treatment of 8 with 2,2-dimethoxypropane and CSA in acetone afforded 8,9-isopropylidene derivative 9 which was selectively benzoylated at O-4 with benzoyl chloride to give monobenzoate 10.…”
Section: Figurementioning
confidence: 99%
“…28,29,70, It can be concluded that the application of 2-chloro derivatives of Neu5Ac gives, in general, good yields when coupled with simple or primary sugar alcohols. 99 As a matter of fact, these methods offer the most reliable approach for the synthesis of simple glycosides of Neu5Ac (see, for example, the synthesis of the strategically important OTE glycosides 100 ). More complex glycosides require modern glycosylation methods which will be discussed in the subsequent sections.…”
Section: A 2-halogeno Derivativesmentioning
confidence: 99%
“…The desired C7-truncated compound 20 was obtained as a minor product but could be readily generated from 21 . Spectroscopic data for 20 were consistent with those previously reported …”
Section: Resultsmentioning
confidence: 99%